Trajetórias escolares, condições de ingresso, permanência e conclusão dos egressos da educação de jovens e adultos na educação superior - PEREIRA, Diego Rodrigo (2018)
This work is linked to the Policy, Educational Management and Human Training Research Line of the Graduate Program in Education of Federal University of Maranhão, had as objective of analyzing the school trajectories, admission conditions, permanence and completion of the graduates of the Education of Youth and Adults (EJA) in Higher Education. The research was carried out under the theoretical-methodological reference of historical-dialectical materialism, which subsidized the development of the quantitative-qualitative study that involved students of the Food Technology and Degree in Agricultural Sciences courses of the Federal Institute of Education, Science and Technology of Maranhão (Ifma) / São Luís-Maracanã Campus. In order to broaden the understanding about the research object and try to answer the guiding questions, a bibliographical review was carried out, based on the contributions of HADDAD & DI PIERRO (2000), CAPUCHO (2012), COULON (2017), FEITOSA, LEITE (2013), RIOS (2011), SILVA (2015), among others. The documentary research is based on laws, decrees, resolutions, ordinances and opinions and data from the School Census for the years 2014 to 2017 regarding to enrollments, classes, educational institutions and teachers at the EJA in Brazil, Maranhão and São Luís, as well as an analysis of the individual record of the students enrolled in Ifma with the record of their school life. In the field research, we used data collection instruments such as questionnaires and interviews applied to 6 students in the age group 28 to 42 years and semi-structured interviews applied to 3 course coordinators. The data analysis allowed to identify that the problems related to the quality of the Basic Education schools offered by the EJA also considering the socioeconomic conditions of the target public of this modality have made difficult the admission in Higher Education through the concurred examinations of access to the universities. Regarding the permanence, basic learning proves to be unsatisfactory, there are insufficient institutional policies to adopt strategies that make it possible to identify the profile of these incoming students in undergraduate courses, follow-up of their academic experiences, and the implementation of student assistance actions that guarantee their attendance to the institution until the conclusion of the course. In the final considerations, it was shown necessary to invest more in the EJA, so that the popular social classes can glimpse possibilities of entrance, permanence and conclusion of studies in Higher Education, attributing new meanings to their life experiences, possibilities for the exercise of citizenship and fully participation in society.